Urgensi Efektivitas Undang-Undang Cipta Kerja Terhadap Ruang Lingkup UMKM Dalam Kesenjangan Ekonomi - Johan Pardamean Simanjuntak; Esra Julita BR PA; Laras Sati Sintania; Salwa Andini; Ramsul Nababan; Maulana Ibrahim (Jaksa : Jurnal Kajian Ilmu Hukum dan Politik, 2024)
This research is entitled "The Urgency of the Effectiveness of the Job Creation Law on the Scope of MSMEs in Economic Disparities" and the aim of this research is to examine improvements or obstacles in business scale, market access and competitiveness as well as finding out changes to employment regulations in the Copyright Law Work influences the protection of labor rights in MSMEs and knowing the concrete efforts in the law to improve the skills and competencies of MSMEs to be more competitive in the market, it is hoped that this research will be the basis for understanding the urgency of the effectiveness of the work copyright law on the scope of MSMEs in theoretical economic inequality.